Clinic management system: business process re-engineering based on user experience (UX) - Lubis, Muharman; Sutoyo, Edi; Handayani, Dini Oktarina Dwi; Azuddin, Muna (Institute of Physics Publishing, 2019)
Clinic management systems function is to arrange and organize the inherent process in the health facility to be harmonized with the patient’s demand. The purpose of this paper is to analyse the common themes to be used in user interface of the application through identification of user specification based on the context. The user experience has been utilized to consider the critical aspect of successes of implementation related to human factor of mental model, which are utility, ease of use and efficiency. The contribution of this paper is twofold. Firstly, the design process should be done through tremendous re-design of primary business process to obtain excessive improvement in the capacity, capability and quality of the service. Secondly, the information presentation should be provided in alternative way involving the effort to have more platform and modes to increase accessibility and availability.